2019
DOI: 10.1186/s13102-019-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wearable physical activity monitoring devices with exercise prescription or advice in the maintenance phase of cardiac rehabilitation: systematic review and meta-analysis

Abstract: Background Physical activity (PA) is a component of cardiac rehabilitation (CR). However, life-long engagement in PA is required to maintain benefits gained. Wearable PA monitoring devices (WPAM) are thought to increase PA. There appear to be no reviews which investigate the effect of WPAM in cardiac populations. We firstly aimed to systematically review randomised controlled trials within the cardiac population that investigated the effect WPAM had through the maintenance phase of CR. We specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 83 publications
4
84
0
Order By: Relevance
“…Recently, a systematic review and meta-analyses evaluating the impact of wearable physical activity monitoring devices in the maintenance phase of CR were published. 14 Three of the nine included studies in this systematic review measured VO 2peak , 3537 and the overall mean difference was 2.24 ml/kg/min, 95% CI 0.58–3.89, 14 which is similar to our result. However, the total number of participants included in this meta-analysis ( n = 133) was just above the number of participants included in our analyses ( n = 102), and time to follow-up ranged from 12 weeks 35,36 to six months.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Recently, a systematic review and meta-analyses evaluating the impact of wearable physical activity monitoring devices in the maintenance phase of CR were published. 14 Three of the nine included studies in this systematic review measured VO 2peak , 3537 and the overall mean difference was 2.24 ml/kg/min, 95% CI 0.58–3.89, 14 which is similar to our result. However, the total number of participants included in this meta-analysis ( n = 133) was just above the number of participants included in our analyses ( n = 102), and time to follow-up ranged from 12 weeks 35,36 to six months.…”
Section: Discussionsupporting
confidence: 86%
“…The exclusion criteria were as follows: ischemia or arrhythmias uncovered at cardiopulmonary exercise test (CPET) that gave restrictions equivalent to <80% of maximal heart rate or BORG scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) <15 at exercise. In addition, patients with muscular or skeletal disorders that affected exercise capacity more than the heart disease were excluded.…”
Section: Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearable devices offer a useful approach for monitoring PA in both clinical research involving patient populations and community-based research (Yingling, et al, 2016). A systematic review and meta-analysis study (Hannan et al, 2019) on the impact of PAT to monitoring exercise prescription or advice in cardiac rehabilitation shown that in 70% of studies, step count was greater in participants using a PAT with exercise prescription or advice, however the overall effect was not significant. Similar results were found by Gal et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…There may be little racial staff diversity, language barriers, and cultural beliefs that add to the patient's lack of CR participation (Rush et al, 2018). Incorporating preferences such as tai chi, dance, yoga may also improve participation (Hannan et al, 2019).…”
Section: Participationmentioning
confidence: 99%